The effects of free range keeping and cage system on the plumage status of Prelux-G laying hens - Terčič, Dušan; Malovrh, Špela; Holcman, Antonija (Acta Agraria Kaposváriensis, 2006)
Plumage damage was measured on hens of Slovenian provenance Prelux-G in two housing systems. Hens were grown from one-day old as a single group on deep litter. At 18 weeks of age, they were randomly assigned to group of 113 hens in a conventional cage system (group I) and to a group of 50 hens and one cock in a free range system (group II). Plumage observations were performed individually at the age of 36 and 72 weeks. The body of a layer was divided into six parts that were measured for denuded areas. Two parts (wings-primary feathers and tail) were examined for damaged and broken feathers. Significantly worse plumage status was found on the head and neck above, head and neck below, breast and wings-coverts at both recordings (36 and 72 weeks) in the group I compared to group II. In contrast, group I had a significantly better feather status on the back compared to group II that is ascribed to the presence of a cock in group II. Denuded areas significantly increased with age for head and neck above in group I, for head and neck below in both groups and for back also in both groups. At the age of 72 weeks more damage for wing primaries was recorded in group I, while more damage for tail feathers was noticed in group II.